Local Influencer Endorsements Impact on Consumer Purchase Intentions: A Replication Study for The Indonesian SMEs - I Made Harry Kurniawan; Hasnul Suhaimi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2021)
Several studies have acknowledged that better access to global financial support is one of the SMEs’ major challenges. However, only a few of them are suggesting alternative feasible strategies to assist SMEs to gain market share against major firms. A considerable approach by SMEs is to promote their products and brands match with SMEs capacities through local influencer endorsement to stimulate consumer purchase intentions. Indonesian culture suggests Islamic religious moral leader figure as a type of influencer which is believed to have a significant influence on consumers’ purchase intention in particular on local social communities. The purpose of this study is to analyze the impact of local influencer endorsements on consumer purchase intentions and the moderating effect of negative publicity on the SME market perspective in Indonesia. A structured questionnaire was created to acquire primary data from 273 respondents using a quantitative research design. The findings from this study indicate that attractiveness, trustworthiness, and familiarity are factors supporting the image of local influencer endorsements, which positively influence consumers’ perceptions of quality, purchase intentions, and brand loyalty. This study also shows that negative publicity on local influencer endorsements does not have a moderating effect on consumer purchase intentions. Keywords: SMEs, influencers, endorsers, purchase intentions, perception of quality, brand loyalty, negative publicit